Nonreciprocal reconfigurable microwave optomechanical circuit - N. R. Bernier (Nature Portfolio, 2017)
Nonreciprocal optical devices traditionally rely on magnetic fields and magnetic-free approaches are rather recent. Here, Bernier et al. propose and demonstrate a purely optomechanical circulator with reconfigurable transmission without the need for direct coupling between input and output modes.